The metacognitive experience of time passing in Chinese college students: scale development, structure verification, and influencing factors - Yu, Xide; Liu, Jiafan; Lin, Yaohui; Chen, Xianli; Lu, Cheng (Frontiers in Psychology, 2023)
The experience of time passing (ETP) is also the consciousness of the progress of life. ETP contributes to time regulation and life management, which basically conforms to the metacognitive theory. Also, the traditional Chinese cultural approach to time emphasizes ETP. It is an indispensable part of Chinese education and culture to strengthen one’s appreciation of time by emphasizing the passage of time. In combination with the above two points, ETP equals metacognitive experience of time passing (METP) to a certain extent. However, we currently know little about the connotations of METP. To better understand traditional Chinese time culture, and referring to the concept of metacognition and model of time experience as proposed by Western scholars, the current study combined the results of open and semi-structured interviews, to explore the structure of METP in Chinese college students and developed a questionnaire with which to measure it. Using convenience sampling, 2,876 college students were recruited, the interview, and the reliability and validity tests were carried out. 579 college students were tested a second time to investigate the correlation validity between METP and Ruminative Responses, time attitude, and meaning in life. The results led to the development of the METP Scale which contains 15 items and assesses two factors: ruminative and emotional experience of time passing. The two-factor model was well fitted, and invariable in measurements across gender, grade, and major. The internal consistency coefficients of the scale and its two factors ranged from 0.82 to 0.89, the half-point reliability between 0.76 and 0.88, and the retest reliability ranged from 0.77 to 0.78. METP Scale has good correlation validity, meanwhile, the results of regression analysis showed that symptom rumination, positive past, negative present, positive future, and searching for meaning in life significantly predict the intensity of METP.